Science and engineering of short fibre reinforced polymers composites - Fu, Shao-Yun; Lauke, Bernd; Mai, Y. W., 1946- (Woodhead Publishing in materials., 2009)
When fibres in a composite are discontinuous and are shorter than a few millimetres, the composite is called a 'short fibre reinforced composite (SFRP)'. SFRPs have found extensive applications in automobiles, business machines, durable consumer items, sporting goods and electrical industries owing to their low cost, easy processing and superior mechanical properties over the parent polymers. The book summarises recent developments in this area, focusing on the fundamental mechanisms that govern the mechanical properties including strength, modulus, fracture toughness and thermal properties of SFRP materials. This book covers the following topics: extrusion compounding and injection moulding, major factors affecting mechanical performance, stress transfer, strength, elastic modulus flexural modulus, thermal conductivity and expansion, non-linear stress-strain behaviour and fracture mechanics of short fibre reinforced polymers. With its distinguished team of authors, Science and engineering of short fibre reinforced polymer composites is a standard reference for anyone involved in the development, manufacture and use of SFRPs. It will also provide an in-depth understanding of the behaviour of these versatile materials. Reviews the mechanical properties and functions of short fibre reinforced polymer composites (SFRP)Examines recent developments in the fundamental mechanisms of SFRP'sAssesses major factors affecting mechanical performance such as stress transfer and strength.